Awakening the Abdullah Badawi years in Malaysia - Welsh, Bridget; Chin, James U.H (Strategic Information and Research Development Centre (SIRD), 2013)
Tun Abdullah bin Haji Ahmad Badawi served as Prime Minister of Malaysia from 2003 to 2009. Better known as Pak Lah, he came in office with a huge mandate. In the 2004 General Elections, the ruling Barisan Nasional (BN) won its best performance since 1969. Five years later in the 2008 GE, the BN won only 140 of 222 seats, a net loss of 58 seats. More importantly it meant the BN lost its customary two-thirds majority in parliament. More than thirty authors, Malaysians and non-Malaysians, give an assessment of the one-term Abdullah administration. The central theme of the book is the question: how did Tun Abdullah change the Malaysian political landscape? This volume offers a comprehensive glimpse of the Abdullah administration from both inside and outside the administration.